Detection of Haemolysin and Tetracycline Resistance Genes in Listeria ivanovii isolated from Foods (Journal of Biochemistry, Microbiology and Biotechnology, 2024)
Listeria ivanovii is an important pathogen that is associated with foodborne diseases. It is responsible for listeriosis in animals, and sporadic cases are present in humans. Drug resistance and virulence among pathogens has been a global health management challenge. This research examined Listeria ivanovii from a few food items for the presence of haemolysin and tetracycline resistance gene. Twenty-five samples each of beef, chicken, lettuce, and cabbage were gathered from four separate locations, for a total of four hundred food samples. The percentage of Listeria ivanovii isolates that were resistant to ampicillin, oxacillin, tetracycline, and clindamycin was 25, 53, 22, and 31%, respectively. Listeria grayi was 23% resistant to cefoxitin, clindamycin and oxacillin. Listeria welshimeri isolate was not resistant to any of the isolates. Two isolates of Listeria grayi and sixteen isolates of Listeria ivanovii were found to be multidrug resistant. The PCR amplification showed that 14.3% of the isolates of L. ivanovii among the selected isolates harboured haemolysin (hylA) gene, 28.6% of isolates harboured tetA gene and 42.9% isolates had tetM gene.
Keywords: Antibiotic; Food; Listeriosis; Resistance Gene; Virulence